2014
DOI: 10.1111/ajo.12267
|View full text |Cite
|
Sign up to set email alerts
|

Impact of using the international association of diabetes and pregnancy study groups criteria in South Auckland: prevalence, interventions and outcomes

Abstract: Adopting the modified IADPSG criteria will result in a 62% increase in the number of GDM cases with a significant impact on workload and resources. Currently, there is insufficient evidence to support the introduction of the IADPSG criteria for our service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
1
26
1
2
Order By: Relevance
“…To our knowledge, this is the first study to compare the perinatal outcomes of women with GDM diagnosed by the 1998 ADIPS and proposed IADPSG criteria. Other studies comparing the IADPSG criteria with various other diagnostic criteria have shown increases in the incidence of GDM, but the influence upon perinatal outcomes has been variable . This variability likely represents the impact of differing demographic characteristics of the populations assessed and the differing diagnostic criteria compared.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to compare the perinatal outcomes of women with GDM diagnosed by the 1998 ADIPS and proposed IADPSG criteria. Other studies comparing the IADPSG criteria with various other diagnostic criteria have shown increases in the incidence of GDM, but the influence upon perinatal outcomes has been variable . This variability likely represents the impact of differing demographic characteristics of the populations assessed and the differing diagnostic criteria compared.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported varied perinatal outcomes in untreated women meeting IADPSG criteria compared to women without GDM. A United States cohort with a large African‐American contingent found increased fetal overgrowth, a Canadian study found no difference, a New Zealand study (55% Maori or Pacific Islander) found increased birthweight and induction, and a Western Australia study (predominantly Caucasian women) reported increased birthweight and macrosomia . Compared to the aforementioned studies, in our larger multicultural cohort with adjustment for confounders including BMI and region of birth, we found that IADPSG‐only criteria identified women and babies with increased risk of gestational hypertension, caesarean section, LGA and shoulder dystocia.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria (fasting plasma glucose (FPG) ≥5.1 mmol/L, and/or one hour glucose ≥10 mmol/L and/or two hour glucose ≥8.5 mmol/L) have caused substantial debate and are variably endorsed by international societies due to concerns regarding increases in diagnosis and health service demands without clear evidence for improved outcomes . There are multiple studies internationally examining the impact of IADPSG criteria on perinatal outcomes with inconsistent findings …”
Section: Introductionmentioning
confidence: 99%
“…The effects of changes in cut-off values of FBG and 2HG on the detection rate of GDM and pregnancy outcomes have been reported 7,8 . However, studies of the additional 1HG test on the pregnancy outcomes are limited.…”
Section: Introductionmentioning
confidence: 99%